Integration and Application of Information and Energy Technologies in Computing Power Integrated Energy Systems - ZHANG Tian, GAO Jianwei, LIU Haoyu, LIU Jiangtao, TAN Qinliang (Dianli jianshe)
The computing power integrated energy system （CPIES）， as a new type of energy system framework， realizes the intelligent management of energy production， transmission， storage， consumption， and information processing by integrating computing and energy resources with the acceleration of digital transformation and the popularity of renewable energy. First， the system architecture and key components of the CPIES， development status and trend， and the interaction mechanism between computing power and energy are outlined. Second， an in-depth analysis of the basis for the integration of information and communication technology （ICT）， artificial intelligence （AI）， big data analysis， and the internet of things （IoT） with the CPIES is presented to promote the intelligence and efficiency of energy systems. Furthermore， the application of information and energy technologies in CPIES is described in detail， demonstrating their potential to enhance energy utilization efficiency and other aspects. Finally， advanced international CPIES projects are listed， the challenges faced by current projects are identified， and countermeasures are suggested. The research results not only help to promote the theoretical development and practical application of CPIES but also provide new ideas and solutions for the digital transformation and sustainable development of the energy industry.